Origination vs Continuation: Ethical Dilemmas of Digital Identity in Robert J. Sawyer’s Mindscan - Bhandari, Uma (NPRC Journal of Multidisciplinary Research, 2025)
Background: Robert J. Sawyer’s science fiction novel Mindscan explores a future where human consciousness can be uploaded into synthetic bodies, offering technological immortality. This premise forces a critical examination of personal identity, posing the central dilemma of whether such a process constitutes genuine survival ("continuation") or merely creates a sophisticated copy ("origination").Objective: This paper aims to analyze the ethical, philosophical, and societal tensions arising from digital identity in Mindscan. It interrogates the novel’s speculation on whether mind-uploading preserves personhood or creates a discrete entity, and it investigates the practical challenges such technology would pose to legal, social, and emotional frameworks.Methods: The research employs a conceptual analysis of Sawyer’s narrative through the critical lenses of philosophers skeptical of human enhancement, primarily Nicholas Agar and Stephen Cave. Their arguments on personal identity and the illusion of technological immortality provide the primary framework, complemented by Mark Coeckelbergh’s insights on relational personhood and moral status.Findings: The analysis concludes that Mindscan presents mind-uploading as an "identity illusion" that benefits a copy rather than ensuring the survival of the original biological self. The novel dramatizes the inadequacy of existing legal and social institutions to accommodate digital beings, highlighting issues of rights, inheritance, and discrimination. Furthermore, it critiques how this technology would exacerbate social inequality by making immortality a luxury commodity.Conclusion: Sawyer’s work serves as a cautionary meditation, suggesting that the pursuit of digital immortality through mind-uploading offers a false promise of salvation. It ultimately underscores that genuine personhood is rooted in spatiotemporal continuity and embodied social interaction, which cannot be replicated by mere pattern duplication.Novelty: This study moves beyond purely philosophical debates on identity to focus on the practical implications of digital consciousness, including legal personhood, economic disparity, and societal integration, as dramatized in a seminal science fiction text.